Perbandingan Ekstrak Daun Sirih (Piper Betle L.) Dan Ekstrak Daun Srikaya (Annona Squamosa L) Dalam Mematikan Lalat Rumah (Musca Domestica) - Hidayat; Ayu Puspitasari; Nia Humaira Shafar (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Houseflies are one of the vector animals or mechanical transmissions, namely, animals that transmit and spread various infectious diseases, one of which is diarrhea. Many fly control methods are known and used by the community, including botanical pesticides. Some plants that can be used as a natural pesticide are betel leaf and soursop leaf, which contain active compounds. The purpose of this study is to determine the ability of betel leaf extract (Piper Betle L.) and soursop leaf (Annona Squamosa L.) as a natural pesticide in killing houseflies (Musca domestica). The tools used in this study were scales, measuring cups, filters, rotary evaporators, fly cages, and the materials used were betel leaves, soursop leaves, 96% methanol, and clean water. The procedure for making the extract was to cut the leaves into small pieces, wash them thoroughly, air-dry them, and weigh as much as 1000 grams. Then, the leaves were put into a jar and soaked with 1000ml of methanol. Do the first soaking for 3 days, stir occasionally, and repeat the procedure for 2 times. Then, separate the leaf pulp and extract, and the leaf extract is evaporated using a rotary evaporator. The results obtained from this study are that soursop leaf extract is more effective in killing houseflies at concentrations of 45% and 50% because it has reached ≥80% and can kill houseflies at two concentrations compared to betel leaf extract, which is only able to kill houseflies at one concentration, namely at a concentration of 50%. This study concludes that the ability of soursop leaf extract to kill houseflies is more effective than betel leaf extract.